Expectations and final evaluation of complete dentures by patients, dentist and dental technician - Marachlioglou, C. R. M. Z.; Dos Santos, J. F. F.; Cunha, V. P. P.; Marchini, L. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
There is a poor association between the dentist's evaluation of denture quality and patients' satisfaction with their dentures. Possible differences between dental professionals and patients' expectations might help explain differences in outcome evaluations. This study compared scores given by a dentist, a dental technician and patients for their expectations before and their final evaluation after complete dentures treatment. Twenty completely edentulous patients, a prosthodontist and a dental technician provided scores for the expected aesthetic and functional results of their dentures based on a visual analogue scale at baseline. Post-treatment completion ratings were given after adjustments, by dentist and patients. The dental technician provided post-treatment completion ratings after completing the dentures. The patients had higher expectations than the dental technician and the dentist perceived for both aesthetic and function (P < 0.001). The patients also presented higher post-treatment completion ratings than the dental professionals perceived for final aesthetics (P = 0.016, Kendall's W = 0.207). and function (P = 0.002, Kendall's W = 0.303). Only the dentist presented a statistically significant difference between expectations (lower) and final (higher) outcomes for aesthetics (P = 0.017) and function (P = 0.003). There was no correlation between expectations and post-treatment completion ratings according to the patients' age. There was also no correlation between the patients' gender and expectation scores. Patients presented higher expectations regarding their dentures than dental professionals. The dentist believed that dentures would bring fewer benefits than patients did, but his perception of denture benefits post-treatment was significantly higher than his expectations.
Keywords: complete dentures; expectations; satisfaction; dentist; dental technician; patients